Timeliness and completeness of laboratory-based surveillance of COVID-19 cases in England. (May 2021) - Clare, T.; Twohig, K.A.; O'Connell, A.-M.; Dabrera, G.
Abstract: Objectives: The aim of the study was to evaluate completeness and timeliness of the rapidly developed surveillance of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in England using patient-level data. Study design: This is an observational study wherein public health surveillance systems are evaluated. Methods: Data were collected in the Public Health England's Second-Generation Surveillance System through routine laboratory reporting processes, as well as via enhanced testing in collaboration with commercial partners. Three periods were chosen to present developments in disease surveillance around the first pandemic wave in England. Completeness of valid entries for key demographic and epidemiological fields was summarised. Timeliness was assessed using recorded date intervals: from sample collection to the laboratory reporting a positive result, the positive result being received by the national surveillance system and the data being available for epidemiological analysis. Results: In each period, demographic variables were more than 95% complete and enhanced ethnicity more than 85%, allowing a rich understanding of the general characteristics of COVID-19 cases in England. The proportion of cases completing all reporting stages of the national system within 3 days of when the specimen was taken increased from 69.1% in period 1 to 76.6% in period 3. In period 3, the median number of days to complete all reporting stages decreased to 2, from 3 in previous periods. Analysis of each reporting stage offers suggestive evidence that timeliness of the system has improved as reporting has become established over time. Conclusions: Timely processing of data for epidemiological use was consistent and rapid once received by the national system. Delays in timeliness were most likely to occur in the first stage of the reporting process, before laboratory input to the surveillance platform. Existing national surveillance mechanisms enhanced during the response have succeeded in providing rapid collection and reporting of case data to facilitate epidemiological monitoring and analysis and guide public health policy and strategy.